MicroRNA expression patterns in oral squamous cell carcinoma: hsa‐mir‐99b‐3p and hsa‐mir‐100‐5p as novel prognostic markers for oral cancer. Issue 10 (29th July 2019) - Jakob, Mark; Mattes, Lena M.; Küffer, Stefan; Unger, Kristian; Hess, Julia; Bertlich, Mattis; Haubner, Frank; Ihler, Friedrich; Canis, Martin; Weiss, Bernhard G.; Kitz, Julia
Abstract: Background: MicroRNAs (miRNA) recently evolved as potential cancer biomarkers. Therefore, the aim of the present study was to evaluate the prognostic impact of eight miRNAs connected to oral squamous cell carcinoma (OSCC). Method: Expression levels of hsa‐mir‐21‐5p, hsa‐mir‐29b‐3p, hsa‐mir‐31‐5p, hsa‐mir‐99a‐5p, hsa‐mir‐99b‐3p, hsa‐mir‐100‐5p, hsa‐mir‐143‐3p and hsa‐mir‐155‐5p were analyzed in tumor tissue (n = 36) and healthy oral mucosal tissue (n = 17) and correlated with clinical variables. Results of the study cohort were validated in an OSCC cohort of The Cancer Genome Atlas . Results: Increased hsa‐mir‐99b‐3p expression level showed a tendency toward advanced tumor stages, and high levels of hsa‐mir‐100‐5p expression were associated with extracapsular extension. While a high expression level of hsa‐mir‐99b‐3p was associated with better survival, a high expression level of hsa‐mir‐100‐5p was correlated with a poorer survival in the study cohort. Conclusion: Our results indicate that hsa‐mir‐99b‐3p and hsa‐mir‐100‐5p may serve as novel prognostic biomarkers in OSCC.